Exploring Senior High School Students Speaking Confidence During Pair Work Activities - Sari, Puspita; Mashuri, Mashuri; Wahyudin, Wahyudin; Marhum, Mochtar (Journal of English Language and Education, 2025)
This study investigates the role of pair-work activities in developing students’ speaking confidence at SMAN 5 Palu. Using a descriptive qualitative research design, four Grade 11 students were purposively selected based on varying levels of speaking confidence. Data were collected through classroom observation, semi-structured interviews, and documentation. The findings reveal that pair-work activities create a supportive, low-anxiety environment that encourages students to speak more freely. Students reported feeling more comfortable, less nervous, and more motivated when interacting with a peer instead of speaking individually or in front of the whole class. Despite challenges such as limited vocabulary, pronunciation difficulties, and fear of making mistakes, pair-work activities helped reduce anxiety and increased communication effort. The study concludes that pair-work is an effective strategy for improving speaking confidence and suggests that teachers integrate more structured and supportive pair-speaking tasks in classroom practice.